Analisis dan Perancangan Kebutuhan Sistem Informasi Kemahasiswaan dan Alumni untuk Meningkatkan Kinerja Lembaga Menggunakan Metode Analisis SWOT - Sipa Nursapa’ah; Sarmidi Sarmidi; Muhammad Taufiq (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2025)
This study explores the need for an integrated information system at the Student and Alumni Development Institute (LPKA) of Universitas Muhammadiyah Tasikmalaya to improve the efficiency of student and alumni data management. The current system does not support digital record-keeping or effective communication with alumni, resulting in suboptimal coordination and limited alumni participation in institutional development. The main objectives are to identify requirements for a web-based information system, analyze internal and external factors using the SWOT method, and design a development strategy aligned with institutional targets. A descriptive quantitative approach was used, with data collected through observation, structured interviews, and questionnaires for active students and alumni. Analysis utilized IFAS and EFAS matrices to determine strategic positioning via SWOT. Findings indicate the need for features such as real-time data management, alumni tracer studies, digital reporting, system integration, and responsive two-way communication. SWOT analysis places LPKA in quadrant I (aggressive), suggesting opportunities for digital expansion by leveraging internal strengths and external opportunities. System implementation is expected to enhance operational efficiency, strengthen alumni partnerships, and create a digital ecosystem supporting collaboration between the academic community and graduates.